Recalcitrant betas: Intraday variation in the cross-sectional dispersion of systematic risk - Torben Andersen; Martin Thyrsgaard; Viktor Todorov (Quantitative Economics, 2021)
We study the temporal behavior of the cross-sectional distribution of assets' market exposure, or betas, using a large panel of high-frequency returns. The asymptotic setup has the sampling frequency of returns increasing to infinity, while the time span of the data remains fixed, and the cross-sectional dimension of the panel is either fixed or increasing. We derive functional limit results for the cross-sectional distribution of betas evolving over time. We demonstrate, for constituents of the S&P 500 market index, that the dispersion in betas is elevated at the market open and gradually declines over the trading day. This intraday pattern varies significantly over time and reacts to information shocks such as clustered earning announcements and releases of macroeconomic news. We find that earnings news increase beta dispersion while FOMC announcements have the opposite effect on market betas.
Keywords: C51; C52; G12; 330; Asset pricing; cross-sectional dispersion; functional convergence; high-frequency data; intraday variation; market beta; nonparametric inference; systematic risk